Hypothesis Testing, "Dutch Book" Arguments, and Risk. Issue 5 (December 2015) - Malinsky, Daniel
Abstract : "Dutch Book" arguments and references to gambling theorems are typical in the debate between Bayesians and scientists committed to "classical" statistical methods. These arguments have rarely convinced non-Bayesian scientists to abandon certain conventional practices (like fixed-level null hypothesis significance testing), partially because many scientists feel that gambling theorems have little relevance to their research activities. In other words, scientists "don't bet." This article examines one attempt, by Schervish, Seidenfeld, and Kadane, to progress beyond such apparent stalemates by connecting "Dutch Book"–type mathematical results with principles actually endorsed by practicing experimentalists.